Micropore Structure and Fractal Characteristics of Clays Due to Freeze-Thaw and Compression Based on Mercury Intrusion Porosimetry - Wang, Shengfu; Lv, Liang; Xue, Kaixi; Zhang, Dongjie; Li, Mingdong; Li, Dongwei; Yuan, Chang (Frontiers in Earth Science, 2022)
The artificial ground freezing method has been widely used in shield end reinforcement and connecting channel reinforcement of urban subway tunnel in water-rich soft soil. Accurate quantification of micropore change and redistribution due to freeze-thaw is important to understand frost heave and thaw settlement of soft soils including mucky clay and silty clay. This paper presents Mercury Intrusion Porosimetry (MIP) data for mucky clay and silty clay specimens before and after freeze-thaw and compression. MIP tests were conducted on the soil samples of undisturbed soil, frozen-thawed soil, compressed soil and compressed frozen-thawed soil. The pores of clays were divided into five groups according to the diameter, including 1) macro pore, 2) medium pore, 3) small pore, 4) micro pore, 5) ultramicro pore. Micro pores and ultramicro pores account for more than 80% of clays’ total pore volume and pore surface area. The pore distribution characteristics of mucky clay and silty clay were studied, and the pore volume and pore surface area distributions’ capacity dimension was estimated. The particle contact, pore changes of clays due to freeze-thaw and compression were analyzed quantitatively. Total pore volume and pore surface area of clays increased due to freeze-thaw, and decreased due to compression correspondingly. The distribution of clays’ pore volume and pore surface area have statistical self similarity, and it is effective to quantify the microstructure changes of clays due to freeze-thaw and compression by estimating capacity dimension, which can provide a new way to reveal the internal micro-pore change of clays due to freeze-thaw and compression quantitatively.